Magnetostructural coupling induced magnetocaloric effects in Ni–Mn-Ga-Fe microwires. (September 2019) - Liu, Yanfen; Luo, Lin; Zhang, Xuexi; Shen, Hongxian; Liu, Jingshun; Sun, Jianfei; Zu, Ningning
Abstract: Ferromagnetic shape memory Ni–Mn-Ga alloys exhibit magnetostructural coupling during the Curie points, which may alter their magnetocaloric effect (MCE). Here MCE of Ni–Mn-Ga alloy microwires are tuned by Fe-doping. The chemical ordering annealed Ni49·6 Mn25.5 Ga22.6 Fe2.3 (Fe2), Ni49·6 Mn25 Ga21 Fe4.4 (Fe4) and Ni48 Mn26 Ga19.5 Fe6.5 (Fe6) microwires have diameters of 30–50 μm and grain sizes of 2–5 μm. The magnetic entropy changes (Δ S m ) of the microwires increase with external magnetic fields, then reach a positive peak and finally decrease to negative peak at a high field. The direct (negative Δ S m, DMCE) and inverse (positive Δ S m, IMCE) MCEs are attributed to microscopic and mesoscopic couplings in microwires. In addition, the specific features of MCEs are also controlled by the magnetization difference (Δ M ) between martensite and austenite phases. Interestingly, the DMCE and IMCE are component dependent. At high Δ M, the linearly decreasing region is dominant and Fe4 and Fe6 microwires produce a negative Δ S m at high magnetic fields due to the microscopic coupling with free electron valence ratio e / a = 7.692 and 7.725. On the other hand, the Δ M is small in Fe2 microwire, which has a positive Δ S m because mesoscopic coupling is dominant with e / a = 7.607; the Δ S m is highest when a single variant martensite occurs, then decreases linearly with increasing magnetic fields. The transition from positive to negative values in Δ S m with the applied fields is related to the counterbalance of mesoscopic and microscopic couplings at e / a = 7.66. Graphical abstract: The study found that, the specific features of the MCE in the present Ni–Mn-Ga-Fe microwires have been found to be controlled by the magnetization difference between martensite/austenite phases (Δ M = M M - M A ). At small Δ M, the ΔS m is first positive, reaches a maximum under a critical magnetic field (e.g. 7.6 kOe for Fe2 where a single variant martensite state occurs), and decreases linearly with H for higher fields. For high values of Δ M, the linearly decreasing region is dominant (e.g. Fe6).Image 1 Highlights: Ni–Mn-Ga-Fe microwires with fine grains were fabricated by melt-extraction. The mixed direct and inverse MCEs caused by the magnetostructural coupling. The MCE can be adjusted by changing the content of Fe.